Power over Deforestation on the Selected News Articles about Diamond Mining in Buxwaha Forest, India - Vivian Zulfie; Sukarno Sukarno; Indah Wahyuningsih (ITScience (Information Technology and Science), 2023)
Deforestation for mining can threaten the balance between human life and nature. This research was aimed to reveal language and power in some media to report deforestation in Buxwaha protected forest of Madhya Pradesh, India. The data were obtained from The Quint and The Times of India as most influential English-language digital media. Fairclough’s CDA theory was used to analyze the data for scrutinizing the connection of language in social use, power, and capitalism as the ideological element. Noticeably, the results showed power represented by local government and mining ministry that tend to accede to the proposed project without considering the ecological collapse Firstly, based on SFL theory, as the textual analysis the total of 40 data proved dominant process of material, mental, and verbal. Secondly, there was bias media to support the mining project by both online newspapers as the discursive practices. Thirdly, in prioritizing the beneficial business, India as a developing country and private company were elaborated as the socio-cultural contexts. Thus, this research expectantly participated to reconsider awareness on the ignorance of deteriorating social and environmental effects for capitalist goals. Keywords: Buxwaha Forest, Capitalism, Deforestation, Language and Power, Mining